Potential Stratospheric Ozone Depletion Due To Iodine Injection From Small Satellites - Wuhu Feng; John M. C. Plane; Martyn P. Chipperfield; Alfonso Saiz‐Lopez; Jean‐Paul Booth (Geophysical Research Letters)
Abstract We use the 3‐D Whole Atmospheric Community Climate Model to investigate stratospheric ozone depletion due to the launch of small satellites (e.g., CubeSats) with an iodine propulsion system. The model considers the injection of iodine from the satellites into the Earth's thermosphere and suggests a 4‐yr timescale for transport of the emissions down to the troposphere. The base case scenario is 40,000 small satellite launches per year into low orbit (100–600 km), which would inject 8 tons I yr−1 above 120 km as I+ ions and increase stratospheric inorganic iodine by ∼0.1 part per trillion (pptv). The model shows that this scenario produces a negligible impact on global stratospheric ozone (∼0.05 DU column depletion). In contrast, a 100‐fold increase in the launch rate, and therefore thermospheric iodine injection, is predicted to result in modeled ozone depletion of up to 14 DU (approximately 2%–7%) over the polar regions.